Ethnic fragmentation, public good provision, and inequality in India, 1988 - 2012 - Nishant Chadha; Bharti Nandwani (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Using data from various rounds of the nationally representative NSSO survey between 1988 and 2012, we first construct national, state, and district-level figures for overall, within and between consumption inequality. We find an increase in inequality in India but only since 2004. We also document an increase in between group (or horizontal) inequality over the entire period. We then investigate the impact of ethnic fragmentation and public good provision on inequality. We hypothesize that by lowering the provision of public goods (specifically schools and health facilities), fragmentation will impact the incomes of the poorer sections more than those of the rich and thus increase inequality. Empirical results support this hypothesis. We find that the increase in overall inequality is lower in less fragmented districts, but there is no strong relationship between horizontal inequality and fragmentation or public good provision. This is because public good provision impacts within group inequality but not between group inequality.
Keywords: I24; D63; H41; H42; 330; inequality; growth; within inequality; ethnic inequality; ethnic fragmentation; public good provision